The effect of nutritional educational programs involving parents on the children dietary behaviour: a systematic review of clinical controlled trails - Mohammad Altamimi; Reem Abu Alwafa; Souzan Zidan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Although many efforts have been applied to tackle obesity, it’s still on the rise, especially among children. Recently, many nutritional educational programs have been conducted in schools to reduce the prevalence of obesity and overweight. The aim of this systematic review is to investigate how effective these programs on the participants' dietary behavior and how far their effect can prevent childhood obesity and overweight if parents/guardians have been involved. Studies were systematically reviewed after searching the Pubmed, Questia, and Science Direct databases. Twelve relevant studies involving parents, have met the inclusion criteria, 8 of them had available results. The assessed outcomes of the reviewed studies have included: nutritional knowledge, food intake, anthropometric measurements, and physical activity. Half of the reviewed studies had positive results and the other half has mixed results. However, data showed significant positive improvements in both anthropometric measurements (for girls a significant reduction in the BMI within the interventional group BMI (p = 0.047) and physical activity (Interventional group mean of steps =13,681 compared to the control mean = 9619 and the attendance in physical education class had increased as well in both genders as well (p = 0.003, p = 0.002) in most studies. It was concluded from the reviewed studies that nutritional educational programs can be an effective prevention action against childhood obesity and overweight with emphasis on the parents as a key role. More efforts from researchers, schools, and stakeholders are required to develop and carry these programs on larger scales and inevitably involving the parents.